Advanced MR Techniques for Preoperative Glioma Characterization: Part 1 - Hirschler, Lydiane; Sollmann, Nico; Schmitz-Abecassis, Bárbara; Pinto, Joana; Arzanforoosh, Fatemehsadat; Barkhof, Frederik; Booth, Thomas; Calvo-Imirizaldu, Marta; Cassia, Guilherme; Chmelik, Marek; Clement, Patricia; Ercan, Ece; et al. (Journal of magnetic resonance imaging, 2023)
Preoperative clinical magnetic resonance imaging (MRI) protocols for gliomas, brain tumors with dismal outcomes due to their infiltrative properties, still rely on conventional structural MRI, which does not deliver information on tumor genotype and is limited in the delineation of diffuse gliomas. The GliMR COST action wants to raise awareness about the state of the art of advanced MRI techniques in gliomas and their possible clinical translation or lack thereof. This review describes current methods, limits, and applications of advanced MRI for the preoperative assessment of glioma, summarizing the level of clinical validation of different techniques. In this first part, we discuss dynamic susceptibility contrast and dynamic contrast-enhanced MRI, arterial spin labeling, diffusion-weighted MRI, vessel imaging, and magnetic resonance fingerprinting. The second part of this review addresses magnetic resonance spectroscopy, chemical exchange saturation transfer, susceptibility-weighted imaging, MRI-PET, MR elastography, and MR-based radiomics applications. Evidence Level: 3 Technical Efficacy: Stage 2.
Keywords: magnetická rezonanční tomografie; nádory mozku; difuzní magnetická rezonance; Brain Neoplasms; Magnetic Resonance Imaging; Humans; Glioma; Diffusion Magnetic Resonance Imaging; gliom; Magnetic Resonance Spectroscopy; lidé; magnetická rezonanční spektroskopie